PENGARUH ONLINE CUSTOMER REVIEW, WORD OF MOUTH, AND PRICE CONSCIOUSNESS TERHADAP MINAT BELI DI SHOPEE - Atma Fadna Rinaja; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (Universitas Bina Taruna Gorontalo, 2022)
The purpose was to determine the effect of Online Customer Review , Word Of Mouth, and Price Consciousness on Buying Interest at Shopee. Type of research is quantitative research. The population in this study were active students of the 2018 and 2019 Faculty of Economics, Universitas Sarjanawiyata Tamansiswa totaling 1,383 then 120 samples. Sampling was carried out using the purposive sampling method. The data collection technique used was a survey method using a questionnaire. Then the data is processed using SPSS IBM Version 23, the data analysis technique used is data quality test, classical assumption test, multiple regression test, t test, and coefficient of determination. Based on the results of this study, online customer reviews have a positive and significant effect on buying interest. this is evidenced by the t-count value of 4.943 and the significant value is shown by 0.000 <0.05. word of mouth has a positive and significant effect on buying interest, this is evidenced by the t-count value of 3.436 and a significant value shown by 0.001 <0.05. Price Consciousness has a positive and significant effect on buying interest, this is evidenced by the t-count value of 3.451 and a significant value shown by 0.001 <0.05.